THE MATHEMATICS OF ASYMMETRIC CRYPTOGRAPHY - BÁRTEK, Květoslav; ZDRÁHAL, Tomáš (Trends in education, 2019)
The RSA cryptosystem is the most widely-used public-key cryptography algorithm in the world. It can be used to encrypt a message without the need to exchange a secret key separately. Its security is based on the difficulty of factoring large integers.
Keywords: cryptography; asymmetric cryptography; RSA encryption; CAS Maxima